The Effects of Work Fatigue and the Work Environment on Employee Performance in SMEs in Cirebon City - Syahniar Diva Rosiyana; Noveria Susijawati (Majapahit Journal of Islamic Finance and Management, 2026)
This study examines the influence of job fatigue (burnout) and the work environment on employee performance in coffee shop SMEs in Cirebon City. The research was motivated by the rapid growth of SMEs and the importance of effective human resource management in businesses with high work intensity. An associative quantitative approach was applied using questionnaires distributed to 97 coffee shop employees selected through purposive sampling. The data were analyzed using multiple linear regression, validity and reliability tests, and classical assumption tests with SPSS version 26. The findings showed that all research instruments were valid and reliable. Regression analysis produced the equation Y = 42.649 + 0.029X1 + 0.486X2. Partial hypothesis testing revealed that job fatigue had no significant effect on employee performance, with a t-count of 0.534 and significance value of 0.594. In contrast, the work environment had a positive and significant influence on employee performance, with a t-count of 6.888 and significance value of 0.000. The adjusted R square value of 0.325 indicates that both variables explained 32.5% of employee performance variation. Overall, the work environment contributed more strongly to performance improvement than job fatigue. Therefore, SME managers should prioritize supportive workplace conditions to enhance employee productivity and organizational sustainability.